Prevalence of Etiological Bacteria and Fungi of Dandruff in Al-Gabal Al-Gharbi, Libya - Adel M. Jama,; Ali Amer Elarabi,; Adah Abish,; Iman Dweila,; Al-Zahra Al-Malawi, (African Journal of Advanced Pure and Applied Sciences, 2025)
The skin hosts a diverse range of microorganisms that influence both its health and disease. Dandruff, a common scalp condition, affects approximately 50% of the global adult population. This study aimed to examine the prevalence of bacteria and fungi in dandruff samples. Materials and Methods: Fifty-two dandruff samples were collected from volunteers in Al-Gabal Al-Gharbi, aged 11–62 years. The samples were cultured for bacterial and fungal growth, followed by microbial identification and sensitivity testing as per routine microbiological procedures. Results: Bacteria were identified in 50 cases (96.15%) and fungi in 35 cases (67.30%). The most common bacterial isolates were Staphylococcus aureus (37.11%) and Staphylococcus epidermidis (24.74%). The most common fungal isolate was Aspergillus niger (29.89%), followed by Aspergillus flavus (3.10%) and Malassezia spp. (5.15%). S. aureus and S. epidermidis were more prevalent in females (58.33% and 54.16%, respectively), while Aspergillus niger and Malassezia spp. were more common in males (44.83% and 60%, respectively). Chloramphenicol exhibited 100% sensitivity against both S. aureus and S. epidermidis, while penicillin and ampicillin showed complete resistance in S. epidermidis. Regarding antifungal activity, Malassezia spp. exhibited full resistance to ketoconazole, while Aspergillus niger was more susceptible to miconazole, with ketoconazole showing 100% resistance.